Representation of Educational and Religious Values as Didactic Literature in the Novel Cinta di Ujung Sajadah by Asma Nadia - Lutfi Dilia; Desliani Zega; Lia Erma Lestari; Nadia Amelia; Sri Kurnia Hastuti Sebayang (Sean Institute, 2026)
Literature not only functions as a medium of entertainment, but also plays an important role as a means of value education through the delivery of reflective moral and spiritual messages. The novel Cinta di Ujung Sajadah by Asma Nadia is one of the Islamic literary works that contains strong educational and religious values ​​​​so it is relevant to be studied as didactic literature. This study aims to analyze the representation of educational and religious values ​​​​as didactic literature in the novel Cinta di Ujung Sajadah. The study uses a qualitative approach with a descriptive analytical method. The main data source of the research is the text of the novel Cinta di Ujung Sajadah, while secondary data are obtained from various books and relevant scientific articles. The data collection technique is carried out through literature studies by reading, recording, and classifying quotations containing educational and religious values. Data analysis is carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study show that the educational values ​​​​in this novel are represented through the life learning process of the characters that shape character, such as responsibility, honesty, and patience. Meanwhile, religious values ​​​​are reflected in the practice of worship, prayer, an attitude of trust, sincerity, and the application of morals in social life. These values ​​are presented narratively and reflectively, avoiding a preachy tone and allowing readers to easily internalize them. Thus, the novel